Masters of death - Blake, Olivie (Tor, Tor Publishing Group, 2023)
"Viola Marek is a struggling real estate agent, and a vampire. But her biggest problem currently is that the house she needs to sell is haunted. The ghost haunting the mansion has been murdered, and until he can solve the mystery of how he died, he refuses to move on. Fox D'Mora is a medium, and though he is also most-definitely a shameless fraud, he isn't entirely without his uses--seeing as he's actually the godson of Death. When Viola seeks out Fox to help her with the ghost infestation, he becomes inextricably involved in a quest that neither he nor Vi expects (or wants). But with the help of an unruly poltergeist, a demonic personal trainer, a sharp-voiced angel, a love-stricken reaper, and a few mindfulness-practicing creatures, Vi and Fox soon discover the difference between a mysterious lost love and an annoying dead body isn't nearly as distinct as they thought"--